Characterization of composites based on recycled expanded polystyrene reinforced with curaua fibers. Issue 1 (11th July 2012) - Borsoi, Cleide; Scienza, Lisete C.; Zattera, Ademir J.
Abstract This study evaluated the mechanical, thermal, rheological, and morphological properties of virgin and recycled matrices and their composites with 20 wt % of curaua fiber. The recycling process of postconsumer polystyrene was carried out by grinding and extrusion. It was found that the recycling of expanded polystyrene did not have a major influence on the mechanical properties; however, the thermal stability was increased. The addition of curaua fibers led to increases in the tensile strength, modulus of elasticity, rigidity, thermal stability and melt viscosity of the composites. The composites made with the recycled matrix revealed higher thermal stability and melt viscosity than those made with the virgin matrix. Scanning electron microscopy characterization showed empty spaces where the curaua fibers had pulled out of the matrices in the fractured regions, indicating poor interfacial adhesion without the use of a coupling agent. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013